Imaging for Transcatheter Edge-to-Edge Repair for Tricuspid Regurgitation in Ebstein Anomaly. (November 2021) - Fan, Yiting; Kam, Kevin; So, Kent; Lam, Yat-yin; Lee, Alex Pui-Wai
Abstract : Supplemental Digital Content is available in the text.